Zastosowanie funkcji kopula w modelowaniu wielowymiarowych czasów trwania na przykładzie decyzji prokreacyjnych aktywnych zawodowo kobiet - Landmesser, Joanna Małgorzata (The Application of Copula Functions to Modeling of Multivariate Durations in the Case of Procreation Decisions Among Professionally Active Women, 2009)
Copulas are a useful method for deriving joint distributions given the marginals especially when we work with non-normal distributions. The aim of our paper is to use this idea in the context of joint duration distributions for the modeling of multivariate survival functions. In our paper, a numerical example is considered, which is based on the data from the German Socio-Economic Panel Study GSOEP. We model the dependence between the duration of time a woman remains childless and the duration of employment among German married women. Marginal models are fitted and tested with the use of standard univariate survival models, and the dependence parameter is estimated in a sequential second-stage procedure. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 398-407